2022
DOI: 10.3390/biomedicines10112948
|View full text |Cite
|
Sign up to set email alerts
|

PTC124 Rescues Nonsense Mutation of Two Tumor Suppressor Genes NOTCH1 and FAT1 to Repress HNSCC Cell Proliferation

Abstract: (1) Background: PTC124 (Ataluren) is an investigational drug for the treatment of nonsense mutation-mediated genetic diseases. With the exception of the TP53 tumor suppressor gene, there has been little research on cancers with nonsense mutation. By conducting a database search, we found that another two tumor suppressor genes, NOTCH1 and FAT1, have a high nonsense mutation rate in head and neck squamous cell carcinoma (HNSCC). PTC124 may re-express the functional NOTCH1 or FAT1 in nonsense mutation NOTCH1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(87 reference statements)
0
2
0
Order By: Relevance
“… 500 Wu et al found that PTC124 (Ataluren) could help HNSCC cells re-express functional Notch1 to substitute the nonsense mutation Notch1, thus preventing the proliferation of HNSCC cells. 501 Taken together, these findings provide evidence that Notch functions as tumor suppressor in relation to SCC, and SCC may be a cancer subtype that could benefit from specific activation of the Notch receptor.
Fig.
…”
Section: The Mechanism Of Notch Signaling Patyway-mediated Tumorigene...mentioning
confidence: 66%
“… 500 Wu et al found that PTC124 (Ataluren) could help HNSCC cells re-express functional Notch1 to substitute the nonsense mutation Notch1, thus preventing the proliferation of HNSCC cells. 501 Taken together, these findings provide evidence that Notch functions as tumor suppressor in relation to SCC, and SCC may be a cancer subtype that could benefit from specific activation of the Notch receptor.
Fig.
…”
Section: The Mechanism Of Notch Signaling Patyway-mediated Tumorigene...mentioning
confidence: 66%
“…Four different p53 nonsense mutations had TGA-type pre-stop codons. Previously, 50 µ M of PTC124 could strongly re-express p53 in SAS HNSCC cells with the E336X mutation, which contains the TAG pre-stop codon [16]. The flowchart of this research and the map of p53 nonsense mutation clones are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, our research has shown that PTC124 can also rescue nonsense mutations in three tumor suppressor genes, p53, NOTCH1, and FAT1, leading to repression of head and neck squamous cell carcinoma (HNSCC) cell proliferation [16]. The p53 gene, encoding a protein with only 393 amino acid residues, has a cDNA of around 1.2 Kb [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it has been found that PTC124 can inhibit head and neck squamous cell carcinoma (HNSCC) cell proliferation by affecting nonsense mutations in two tumor suppressor genes, NOTCH1 and FAT1 (Wu et al, 2022a). Mutant UPF1 was found in pancreatic ductal adenocarcinoma, resulting in overactivated NMD, closely associated with elevated ASNS expression levels.…”
Section: B Practical Application Of Disease-centred Target Discovery ...mentioning
confidence: 99%